Slow recovery of previously depleted demersal fish at the South Shetland Islands, 1983-2010 - Marschoff, Enrique Ricardo (2012)
Following seals and baleen whales prior to the 1970s, demersal fish stocks were depleted off the South Shetland Islands by intensive industrial fishing during the late 1970s to early 1980s. Little has been reported since about how these stocks have fared, after international agreement closed this fishery in 1990. We report changes in size and abundance of the commercially exploited Notothenia rossii and Gobionotothen gibberifrons relative to the ecologically similar but unexploited Notothenia coriiceps at Potter Cove, South Shetland Islands, over a 28-yr period, 1983?2010. N. rossii abundance declined from 1983 to 1991, and an increase in mean size during 1983?1984 is consistent with weak cohorts during preceding years. Modal age changed from 2?3 to 6?7 yr. Length data of G. gibberifrons, available from 1986, exhibited a similar pattern, showing a decrease until 1991?1992. After a period of relative stability (1992?1994), a sharp increase in length and a continued decline in relative abundance indicated low recruitment. The length?frequency distribution of unexploited N. coriiceps throughout the whole period showed no change in modal size or mean length of the fish. We relate these patterns to the fishery and suggest that a further two decades will lapse before these stocks recover. Using the South Shetland fisheries as an example, current management rules for Southern Ocean fisheries, deemed to be precautionary and disallowing depletion beyond which a stock can recover in 2?3 decades, may be unrealistic in an ocean profoundly altered by numerous stock depletions and rapid climate change.